Návrh komunikačního mixu cateringové společnosti - Pelikánová, Adéla (Vysoké učení technické v Brně. Fakulta podnikatelská, 2023)
Diplomová práce se zabývá návrhem komunikačního mixu začínající společnosti. Tyto návrhy přitom vychází z teoretických poznatků z oblasti marketingu, marketingové komunikace a také z analýzy rozborů vnějších a vnitřních faktorů společnosti. Cílem diplomové práce je vytvoření komunikačního mixu pro nově vznikající společnost a návrh vhodných komunikačních nástrojů pro vstup začínajícího podniku na trh.

Master’s thesis deals with the proposal of communication mix for start-up company. This proposals is based on theoretical knowledge of marketing, marketing communications as well as the analysis from the study of external and internal factors of the company. The aim of this thesis is to create a communication mix for a new start-up company and proposal of appropriate communication tools for the entry of start-up company to the market.
Proposal of the Communication Mix for the Catering Company
Keywords: Marketing; marketing služeb; marketingový mix; komunikace; komunikační mix; Marketing; marketing of services; marketing mix; communication; communication mix